Implementing Interagency Collaborations: Exploring Variation in Collaborative Ventures in Human Service Organizations - Sowa, Jessica E. (Administration & society, 2008)
Collaborative mechanisms are increasingly being used to deliver public services in the United States, with many scholars seeking to understand the operation and impact of these ventures. This article contributes to this research by breaking apart interagency collaborations used to deliver services, demonstrating the variations that can occur within a single form of collaborative service delivery. Examining collaborations to deliver early care and education services, this article demonstrates that scholars need to examine multiple collaborative ventures within policy fields to understand the variations that can arise during the implementation process and the implications of these variations for the public services.